2001
DOI: 10.1016/s0304-3959(01)00353-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced development of tolerance to the analgesic effects of morphine and clonidine in PKCγ mutant mice

Abstract: A variety of second messenger systems have been implicated in the intracellular mechanisms of tolerance development to the analgesic actions of morphine, a mu opioid, and clonidine, an alpha-2 adrenergic receptor agonist. Here, we studied mice that carry a null mutation in the gene encoding a neuronal specific isoform of protein kinase C (PKC), namely, PKC gamma. We used the tail-flick test to construct dose-response curves before and 4 days after chronic morphine (75-mg pellets, subcutaneously (s.c.)) or clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 37 publications
6
90
0
Order By: Relevance
“…With the method of [ The results indicate a strong correlation between PKC and morphine tolerance, which was later confirmed by a wide range of other studies (8)(9)(10)(11). The present study was performed to explore the role of PKC in morphine tolerance at the spinal level of rats, especial in the development and maintenance of morphine tolerance.…”
supporting
confidence: 66%
“…With the method of [ The results indicate a strong correlation between PKC and morphine tolerance, which was later confirmed by a wide range of other studies (8)(9)(10)(11). The present study was performed to explore the role of PKC in morphine tolerance at the spinal level of rats, especial in the development and maintenance of morphine tolerance.…”
supporting
confidence: 66%
“…In more recent work, it was demonstrated that PKCγ contributes to the induction of tolerance to morphine. PKCγ knock out mice had similar nocioceptive processing regardless of morphine treatment [74]. In other work, PKCγ knock out mice treated with morphine did not exhibit spinal cord astroglial hypertrophy or proliferation which is normally associated with development of morphine tolerance [75].…”
Section: Pkcγ and Pkcε In Neural Tissuesmentioning
confidence: 72%
“…Morphine tolerance was prevented when mice were co-infused for 5 days with the antisense oligonucleotide to PKC and morphine (Hua et al, 2002). A similar attenuated morphine tolerance was observed in PKC null mutant mice, suggesting that the level of PKC available for kinase phosphorylation is critical to the development of antinociceptive tolerance (Zeitz et al, 2001). We have recently used pseudosubstrate and RACK (receptors for activated C-kinase) peptides inhibitors that can inhibit only a single PKC isoform, and we demonstrated that the PKC , and but not the PKC I , II , , , , and isoforms appear to contribute to the expression of morphine tolerance in mice (Smith et al, 2007).…”
Section: Prevention Of Morphine Antinociceptive Tolerance By Pkc Inhimentioning
confidence: 73%